Assédio moral na relação de emprego e responsabilidade civil do empregador - Rondelli, Cristiane Montenegro (2008)
This thesis aims to give primary reasons to the defense of the employer s objective responsibility in case of moral harassment, to present proposals of acting for prevention of the moral harassment in the work s environment and, principally, to demonstrate the application of the principle of the human dignity in the interpersonal relations in the work s environment. The care with the environment involves also psychological aspects and not only physical. Even appropriate work s environment, than Labor Law are been considered as basic rights, of immediate application and, so, it cannot suffer retreats, according to foresight in the international right and in the Federal Brazilian Constitution, which takes as basic principles the human dignity and the social value of the work. The insults to these principles are susceptible to compensation and other forms of mending and protection for which have suffered material or moral damages. Hereby we offered proposals for prevention of the moral harassment and health s protection and work s security to the enterprise, the trade unions and to the supervisory organs, including the Public Work Ministry